2020
DOI: 10.3390/molecules25102423
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and Sensory Metabolites Profiling of Averrhoa Carambola L. (Starfruit) in the Context of Its Origin and Ripening Stage by GC/MS and Chemometric Analysis

Abstract: Averrhoa carambola L. is a tropical tree with edible fruit that grows at different climatic conditions. Despite its nutritive value and reported health benefits, it is a controversial fruit owing to its rich oxalate content. The present study aimed at investigating aroma and nutrient primary metabolites distribution in A. carambola fruits grown in Indonesia, Malaysia (its endemic origin) versus Egypt, and at different ripening stages. Two techniques were employed to assess volatile and non-volatile metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…Comparing to previous studies, the results of our RSFs extracts' GC-MS analysis differed.. According to a research study conducted in Malaysia, Tridecane, 4-methyl-compound has the highest peak with 13.75 min R.T. At the same time, GCMS analysis of RSFs extracts from Bogor Indonesian, Egypt, and India indicated that the highest peak was Nerylacetone at 4.43 min R.T., Methyl caproate at 7 min R.T. and 9-Octadecenoic acid (Z)-, methyl ester at 22 min R.T. respectively [20,21]. Despite limitations of GC-MS analysis in terms of the mass range and metabolites polarity, using the derivatization technique has expanded the range of separable and detectable chemical compounds in high-throughput profiling research.…”
Section: Identification Of Ecg Compoundmentioning
confidence: 92%
“…Comparing to previous studies, the results of our RSFs extracts' GC-MS analysis differed.. According to a research study conducted in Malaysia, Tridecane, 4-methyl-compound has the highest peak with 13.75 min R.T. At the same time, GCMS analysis of RSFs extracts from Bogor Indonesian, Egypt, and India indicated that the highest peak was Nerylacetone at 4.43 min R.T., Methyl caproate at 7 min R.T. and 9-Octadecenoic acid (Z)-, methyl ester at 22 min R.T. respectively [20,21]. Despite limitations of GC-MS analysis in terms of the mass range and metabolites polarity, using the derivatization technique has expanded the range of separable and detectable chemical compounds in high-throughput profiling research.…”
Section: Identification Of Ecg Compoundmentioning
confidence: 92%
“…The chemical compounds of the identified EOs were extracted using MET-IDEA software with default parameter settings for GC-MS [ 50 ]. The aligned peak abundance data table was further exported to principal component analysis (PCA) using the SIMCA-P version 13.0 software package (Umetrics, Umeå, Sweden).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the proportion of total unsaturated fatty acids existing both in the fruits and leaves of A. carambola comprise more than 77% of total fatty acid ( Wei et al, 2014 ). The fructose content (38–48%) and glucose content (21–25%) have predominantly sugar-based compositions in A. carambola ripe fruits, while sorbitol is also another major sugar alcohol (2.4–10.5%) in ripe fruits ( Ramadan et al, 2020 ). Additionally, the presence of high amounts of fibers in this plant contributes to the absorption of glucose, restraint glucose diffusion into the bloodstream, and maintain normal blood glucose levels ( Fan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%